2014
DOI: 10.1097/mao.0000000000000298
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Advantages of Transcanal Endoscopic Myringoplasty

Abstract: Comparison of microscopic and endoscopic views revealed superior visualization and operability of the endoscopic approach as opposed to transcanal simple underlay myringoplasty. Transcanal endoscopic myringoplasty does not require surgical exposure such as a retroauricular skin incision to get an anterior view. Our results demonstrated that transcanal endoscopic myringoplasty can be performed, regardless of the perforation size and the narrowness and/or protrusion of external ear canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 13 publications
6
80
0
10
Order By: Relevance
“…The perforation closure rate was 80%, and postoperative improvement of ABG was 7 dB. Furukawa [4] reported 25 ears that underwent transcanal endoscopic myringoplasty; a perforation closure rate of 84.0% was obtained, with only one case of reperforation. The improvement in ABG was 10.3 dB.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The perforation closure rate was 80%, and postoperative improvement of ABG was 7 dB. Furukawa [4] reported 25 ears that underwent transcanal endoscopic myringoplasty; a perforation closure rate of 84.0% was obtained, with only one case of reperforation. The improvement in ABG was 10.3 dB.…”
Section: Discussionmentioning
confidence: 92%
“…However, despite providing direct exposure, microscopes require frequent adjustment and may still not be sufficient when encountering protruding structures, particularly the anterior wall. In a study conducted by Furukawa et al [4] , the circumference of the perforation could not be confirmed with a microscope before denuding in 12.0% of cases. Furthermore, the entire perforation was not visible in 20.0% of cases after refreshing the edges.…”
Section: Discussionmentioning
confidence: 99%
“…With endoscopes, the line of sight can be moved closer to the surgical field, allowing more complete surveillance. In addition, endoscopes allow visualization around structures, which is not possible with a conventional microscope and is greatly augmented with angled endoscopes [6,[13][14][15][16] . Accordingly, an increasing number of ear-surgeons nowadays considers otosclerosis to be a suitable disease for endoscopic stapes surgery due to the fact that the endoscopic approach offers excellent visualization of middle ear structures and recesses, mainly the oval window niche, stapes anterior crus, and its suprastructure [5,6,[17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Hearing thresholds including air conduction and bone conduction were measured at 0.5, 1.0, 2.0 kHz, and the pure tone averages were calculated. TM perforation size was expressed as a percentage of the entire TM area using Image J software (National Institutes of Health, Bethesda, MD, USA) 6 . X-ray mastoid was done to know the cellularity of mastoid.…”
Section: Methods:-mentioning
confidence: 99%